The X1 catalogue of positions and proper motions of faint stars around the ICRF sources - Fedorov, P.N.; Myznikov, A.A. (Кинематика и физика небесных тел, 2005)
We present a new catalogue of faint astrometric reference stars around ICRF sources of northern hemisphere. The X1 catalogue is obtained at the Institute of Astronomy of the V.N. Karazin Kharkiv National University and contains about 1.3 million positions and proper motions of stars from 10m to 19m within 330 1° ×1° fields. Mean positions and proper motions of stars were derived from reprocessing and astrometric reduction of digitized images of Schmidt plates POSS-I and POSS-II sky surveys obtained from USNOFS PMM Image Archive. The Tycho-2 stars were used as reference stars. The mean errors of the positions at mean epoch are 50 to 100 mas, depending on magnitude and particular field. Proper motions errors are about 2.5 to 5 mas/yr depending on magnitude. Estimated external errors are close to internal errors mentioned. The source data, brief outlines of the image processing and reduction techniques, main features of the catalogue, as well as some results of external comparisons are presented.